Batteryâs Life-Time Estimation of Industrial WirelessHART Sensor Actuator Node - Tran, D.C. (Springer, 2020)
In industrial applications of wireless technologies, very common, wireless sensor and actuator nodes are installed at fields. Therefore, it is critical to extend batteryâs lifetime for ensuring continuous servicing period of field instruments over years. Apart from periodic battery status update during operations of the nodes, at planning stage, plant management team can estimate batteriesâ lifetime at field wireless instruments for operational budget estimation and preventive maintenance planning. This work proposes a framework to estimate the batteryâs lifetime taken into consideration of periodic update periods and devicesâ operational frequencies. The framework is based on the knowledge of wireless node, microcontrollerâs power consumption, and battery specifications. Based on the analysis, at particular operational conditions (i.e., update period of 512Â s, low-power mode with voltage of 1.8 V), the estimated batteryâs lifetime of a wireless node can reach up to 9Â years. Â© 2020, King Fahd University of Petroleum & Minerals.